Economics of herbicide programs for weed control in conventional, glufosinate, and dicamba/glyphosate‐resistant soybean across Nebraska. (20th October 2020) - Striegel, Adam; Eskridge, Kent M.; Lawrence, Nevin C.; Knezevic, Stevan Z.; Kruger, Greg R.; Proctor, Christopher A.; Hein, Gary L.; Jhala, Amit J.
Abstract: Despite widespread adoption of dicamba/glyphosate‐resistant (DGR) soybean [ Glycine max (L.) Merr.] in Nebraska and across the United States in recent years, economic information comparing herbicide programs with glufosinate‐resistant (GLU‐R) and conventional soybean is not available. The objectives of this study were to evaluate weed control efficacy, crop safety, gross profit margin, and benefit/cost ratios of herbicide programs with multiple sites of action in DGR, GLU‐R, and conventional soybean. Field experiments were conducted in 2018 and 2019 at three irrigated and two rain‐fed locations across Nebraska, for a total of 10 site‐years. Herbicides applied pre‐emergence (PRE) that included herbicides with three sites of action provided 85–99% control of common lambsquarters ( Chenopodium album L.), Palmer amaranth ( Amaranthus palmeri S. Watson), velvetleaf ( Abutilon theophrasti Medik.), and a mixture of foxtail ( Seteria spp.) and Poaceae species. Pre‐emergence herbicides evaluated in this study provided 72–96% weed biomass reduction and 61‒79% weed density reductions compared with the nontreated control. Herbicides applied post‐emergence (POST; dicamba plus glyphosate, glyphosate, glufosinate, and acetochlor plus clethodim plus lactofen) provided 93–99% control of all weed species 28 d after POST (DAPOST). Herbicides applied POST provided 89–98% weed biomass reduction and 86–96% density reduction at 28 DAPOST. For individual site‐years, yield was often similar for PRE followed by POST herbicide programs in herbicide‐resistant (HR) and conventional soybean. Gross profit margins and benefit/cost ratios were higher in HR soybean than in conventional soybean, although price premiums for conventional soybean can help compensate for increased herbicide costs.